Mothers’ perceptions on their child weight: a descriptive study: Mothers and child weight perceptions - Vitale, Elsa; Fortunato, Rosa Silvia; Della Pietà, Cosimo; Ciurlia, Maria Luisa; Germini, Francesco (Progress in Nutrition, 2021)
Objective: This descriptive study examines the relationship between child effective weight and their mothers’ perceptions.Design: A descriptive study was performed to investigate mothers’ perceptions’ on their weight children.Setting: Obesity is considered to be the most important nutritional disease among children in the world.Participants: It was considered a sample of 105 participants 9-10 years. Each school children was assessed in his weight, high. BMI values were evaluated and percentile classes were identify.Then two questions were asked to their mothers in order to understand their perception on their child weight and if this condition could influence the future weight of their sons.Results: A total of 105 schoolchildren and their mothers were enrolled in this study. Of these, 7% (n= 6) of the children were underweight, 43% (n= 23) were normal weight, 23% (n= 16) were at risk to become overweight, indicated as “AROW”, 27% (n= 16) were overweight.Most parents (78%) felt their child had normal weight, 9% of mothers felt their children was underweight and 8% mothers considered their child overweight. Only 5% mothers evaluated the risk to become overweight in their children. Figure 1 compared child weight with mother perception on their child weight. Pearson correlations were assessed to compare child BMI values and their mothers’ perceptions.Conclusion: Mothers underestimated their child weight and future consequences that it concerns.